Effect Of Distance On Wi-Fi Signal Quality In The Home Environment - Putra, Fauzan Prasetyo Eka; Ubaidi, Ubaidi; Kusuma, R. Okky Firmansyah; Syam, Abd Mu’iz; Efendy, Satrio Ananta (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This study aims to analyze the effect of distance on Wi-Fi signal quality in a home environment. With the increasing use of wireless devices and applications that rely on internet connectivity, Wi-Fi signal quality has become crucial to support daily activities such as streaming, online gaming, remote work, and smart home automation. This research employs an experimental method by measuring signal strength and data transmission speed at various distances from the Wi-Fi router. Measurements were taken at several points, ranging from 1 meter to 15 meters from the router, in different rooms and through different obstacles like walls and furniture.To conduct the analysis, a Wi-Fi analyzer was used to measure signal strength (in dBm) and a speed test was employed to determine data transmission speed (in Mbps) at each distance. The results showed that the greater the distance from the router, the Wi-Fi signal strength decreased significantly, leading to a corresponding decrease in data transmission speed. In addition, obstacles such as walls and electronic interference further degraded the signal quality.This study concludes that optimizing router placement and using signal booster devices, such as Wi-Fi extenders or mesh networks, can be effective solutions to improve Wi-Fi signal quality at home. It also highlights the importance of understanding and managing home network infrastructure to maximize Wi-Fi usage efficiency. By strategically placing routers and employing additional network hardware, users can ensure a stable and fast internet connection throughout their home, enhancing the overall user experience and productivity. Research provides valuable insights for homeowners and technology enthusiasts on how to achieve optimal Wi-Fi performance in various home environments.